2000
DOI: 10.1097/00001756-200001170-00008
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of gamma activity in the human medial temporal lobe by sevoflurane anesthesia

Abstract: We have reported the presence of continuous gamma (30-150 Hz) activity in the human medial temporal lobe (MTL). Since the MTL is involved in learning and memory, we speculated that MTL gamma activity is related to such higher brain functions. It is thus of interest to learn how this activity changes during different states of consciousness. In this study, we recorded electrocorticographic (ECoG) activity directly from the surface of the MTL after various doses of sevoflurane anesthesia. Five epileptic patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Possibly this ongoing gamma may represent an idling search mechanism for a meaningful, task related binding of neuronal groups for a specific perceptual task. The presence of an ongoing gamma was also shown in animals (Imas et al [23]) and humans (Uchida et al [18]) undergoing deep anaesthesia.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Possibly this ongoing gamma may represent an idling search mechanism for a meaningful, task related binding of neuronal groups for a specific perceptual task. The presence of an ongoing gamma was also shown in animals (Imas et al [23]) and humans (Uchida et al [18]) undergoing deep anaesthesia.…”
Section: Discussionmentioning
confidence: 82%
“…Uchida and colleagues [18] showed that gamma frequencies are not only demonstrated during repeated intentional activities, but also appear spontaneously during different sleep phases and different degrees of anaesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of anesthetics on γ oscillations has been controversial. Unlike human investigations 1-3 , most experimental studies found that both cortical and hippocampal γ oscillations were preserved or even augmented under general anesthesia 4-9 , thus questioning a presumed unitary correlation between γ activity and consciousness. A notable exception is the study by Ma et al 10 that found some correlation between hippocampal γ oscillations and consciousness in rats.…”
Section: Introductionmentioning
confidence: 89%
“…In addition to assessing behavioral response to pain and righting, we recorded neocortical and hippocampal EEGs. Neocortical slow waves, or delta waves of o4 Hz (Rampil, 1998;Steriade, 2003) and hippocampal theta (4-10 Hz) (MacIver et al, 1996;Vanderwolf, 1988) and gamma (30-100 Hz) rhythms (Leung et al, 1982;Uchida et al, 2000) are known to be indicators of sleep-wake behaviors and levels of consciousness. Some of the results have been presented in an abstract form (Ma et al, 2003).…”
Section: Introductionmentioning
confidence: 99%